Highest primary production achieved at high nitrogen levels despite strong stoichiometric imbalances with phosphorus in hypereutrophic experimental systems. Issue 12 (18th November 2021) - Kelly, Patrick T.; Taylor, Jason M.; Andersen, Isabelle M.; Stovall, Jasmine; Scott, J. Thad
Abstract: Lakes in human‐dominated landscapes often face high loads of nutrients that may alter ecosystem function. High N loads relative to P are especially common in agricultural watersheds, where nitrate (NO3 ) in particular is elevated due to fertilizer application and runoff. While past research has focused extensively on the impact of nutrient loads on reductions in water quality, we still lack assessment of the impact of high N loading and extreme stoichiometric imbalance on ecosystem process rates, specifically measurements of gross primary production (GPP), ecosystem respiration (ER), and net ecosystem productivity (NEP). We used open‐bottomed experimental mesocosms (limnocorrals) to establish four treatments of increasing N : P by increasing N loads while leaving P loads consistent, and measured chlorophyll concentration and metabolic rates. We observed significant differences in productivity among treatments, with higher biomass and GPP in the highest two N : P treatments and a unimodal pattern between GPP and N concentrations. Declines in GPP at high N may have been due to limitation by P or light. In contrast to other studies, we did not observe any significant differences in ER with fertilization, potentially from a lack of dissolved organic carbon loading often associated with higher nutrient concentrations in those lakes. Maximum GPP and NEP observed here was far above commonly cited thresholds for likely P limitation at a molar N : P of approximately 330. Our results highlight the potential for high productivity despite stoichiometric imbalance that is common in agricultural systems, suggesting N management may be important in reducing primary production in hypereutrophic lakes.